FACTORS THAT EFFECT THE PERFORMACE OF GOVERNMENT OFFICIALS SENGATA DISTRICT NORTH EAST KUTAI - Setiawan, Heri (EKONOMIA, 2013)
Problems in this study were : 1) What are the factors physiologi need, safety needs, socialization needs, esteem needs and self-act-actualization needs significant effect in the performance of government officials Sangatta northern districts. 2) Whicj factors most influence on employee performance Sangatta northern district administration, basic theory of human resource management include motivation theory and performance theory. The hypothesis of this pernulisan formulated as follows. 2) There is a significant effect between physiologi needs, safety needs, socialization needs, esteem needs and self-actualization needs on the performance of employees in the district administration Sangatta north east Kutai regency. 2) penghargaan needs to have the most impact on the performance of gobernment officials Sangatta north east Kutai district. In an attempt to solve the problems associated with the use of writing in the statistical analysis with the help of the program SPPS ver. 19.0 (statiscal program for Social Science) as follows : Y = a + b1X1 b2x2 + + + b3X3 b4X4 b5X5 + + e.Based on the analysis and discussion, it can be concluded : of the five independent variables were studied, all have a positive effect. This shows the increasing demand followed by increased employee performance. Functional relationship Variables-variables that influence employee performance formula produces multiple regression equation as follows :Y = 0.321 + 0.144 + 0.138XI + 0.157X2 + 0.256X3 + 0.232 X4 X5Empirical evidence to determine the test results calculated F Value of 22.639 > of the F table at 2.5336 and significant at 0.000, from 0.05 then the probability of the hypothesis that the simultaneous influence of independet variables on the dependet variable employee performance accptable.Variable physiologi safety, socialization, and self-actualization awards simultaneously have a positive and significant relationship with the performance of goverment officials Sangatta north east Kutai district.Partial variabel that has meaning physiologi employee performance is variable, safety, socialization, respect and self-actualization of the five variables are variables awards have the most impact on the performance of goverment official Sengata north east Kutai district. Strengh of this correlation is evidenced in the test variable parial 0.000 awards with a smaller probability of a = 5% as a starting measuring obtained t value of 7.066. from the t table with r2 = 2.0639 + 0.700 or 70%. Thus the hypothesis that award needs factors have the most influence on the performance of goverment official Sengata north East Kutai district received.